2014
DOI: 10.1155/2014/275083
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical Logic Gates: Designs, Classification, and Comparison

Abstract: The paper reviews the current status and designs of all-optical gates. Various schemes with and without semiconductor optical amplifiers are discussed and compared. The optical gates are classified according to their design structures. It is divided into two major divisions that is, nonsemiconductor optical amplifier based gates and semiconductor optical amplifier based gates. In nonsemiconductor optical amplifier based gates, different schemes have been proposed to create non-linearity which is discussed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 67 publications
0
51
0
Order By: Relevance
“…All-optical signal processing fundamentally relies on modulation of one optical signal with another. Therefore all-optical logical functions have long been perceived as the exclusive domain of nonlinear optics [1], which requires a minimum level of intensity to activate the nonlinear material response and faces trade-offs between magnitude and speed of the nonlinearity involved [2][3][4][5][6]. However, recently it was shown that an effective nonlinear response may be derived from coherent interaction of light with light on linear materials of substantially subwavelength thickness [7].…”
mentioning
confidence: 99%
“…All-optical signal processing fundamentally relies on modulation of one optical signal with another. Therefore all-optical logical functions have long been perceived as the exclusive domain of nonlinear optics [1], which requires a minimum level of intensity to activate the nonlinear material response and faces trade-offs between magnitude and speed of the nonlinearity involved [2][3][4][5][6]. However, recently it was shown that an effective nonlinear response may be derived from coherent interaction of light with light on linear materials of substantially subwavelength thickness [7].…”
mentioning
confidence: 99%
“…In this section, we briefly discuss the scheme and operation principle of all-optical gates which are core logic units for the all-optical signal processing system implementation [9]. All-optical gates may be divided into two groups: without SOA and with SOA [9]. The all-optical gates without SOA are based on the change in nonlinear refraction index in silica fiber [9].…”
Section: All-optical Logic Gates With Soamentioning
confidence: 99%
“…1 Materials containing photo-responsive dyes have been found to be suitable for such a task and therefore become attractive in the field of optical communication and high-density optical data storage. [16][17][18] Azo-dye containing polymers are usually known for the large photoinduced linear birefringence that makes them attractive for reversible optical storage and other optical applications.…”
Section: Introductionmentioning
confidence: 99%